WAYS TO IMPROVE FREE ECONOMIC ZONES IN REGIONAL DEVELOPMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The financial ecosystem within free economic zones greatly influences their overall attractiveness. Access to diverse sources of financing, whether through banks, non-banking institutions, venture capital, or leasing, allows companies to expand, innovate, and remain competitive. Policies should encourage the presence of financial intermediaries and foster a climate conducive to the creation and scaling up of enterprises. Special attention needs to be given to facilitating cross-border financial transactions, which are vital for integrating regional economies into global value chains.